Tigers and Their Prey in Bukit Rimbang Bukit Baling: Abundance Baseline for Effective Wildlife Reserve Management - Febri Anggriawan Widodo; Stephanus Hanny; Eko Hery Satriyo Utomo; Zulfahmi Zulfahmi; Kusdianto Kusdianto; Eka Septayuda; Tugio Tugio; Effendy Panjaitan; Leonardo Subali; Agung Suprianto; Karmila Parakkasi; Nurchalis Fadhli; Wishnu Sukmantoro; Ika Budianti; Sunarto Sunarto (Fakultas Kehutanan Universitas Gadjah Mada, 2017)
Managing the critically endangered Sumatran tiger (Panthera tigris sumatrae) needs accurate information on its abundance and availability of prey at the landscape level. Bukit Rimbang Bukit Baling Wildlife Reserve in central Sumatra represents an important area for tigers at local, regional and global levels. The area has been recognized as a long-term priority Tiger Conservation Landscape. Solid baseline information on tigers and prey is fundamentally needed for the management. The objective of this study was to produce robust estimate of tiger density and prey a vailability in the reserve. We used camera traps to systematically collecting photographic samples of tigers and prey using Spatial Capture Recapture (SCR) framework. We estimated density for tigers and calculated trap success rate (TSR; independent pictures/100 trap nights) for main prey species. Three blocks in the reserve were sampled from 2012 to 2015 accumulating a total of 8,125 effective trap nights. We captured 14 tiger individuals including three cubs. We documented the highest density of tigers (individuals/100 km2) in southern sampling block (based on traditional capture recapture (TCR) : 1.52 ± SE 0.55; based on Maximum Likelihood (ML) SCR:0.51 ± SE 0.22) and the lowest in northeastern sampling block (TCR: 0.77 ±SE 0.39; ML SCR: 0.19 ± SE 0.16). The highest TSR of main prey (large ungulates and primates) was in northeastern block (35.01 ± SD 8.67) and the lowest was in southern block (12.42 ± SD 2.91). The highest level of disturbance, as indicated by TSR of people, was in northeastern sampling block (5.45 ± SD 5.64) and the lowest in southern (1.26 ± SD 2.41). The results suggested that human disturbance strongly determine the density of tigers in the area, more than prey availability. To recover tigers, suggested strategies include controlling human disturbance and poaching to the lowest possible level in addition to maintaining main prey availability.Keywords: Capture-Mark-Recapture; closed population; habitat management; population viability; tiger recovery Harimau dan Mangsanya di Bukit Rimbang Bukit Baling: Basis Informasi Kelimpahan untuk Pengelolaan Suaka Margasatwa yang EfektifIntisariMengelola spesies kunci seperti harimau Sumatera (Panthera tigris sumatrae) yang dalam kondisi kritis, memerlukan informasi terkait populasi satwa tersebut dan ketersediaan satwa mangsanya pada tingkat lanskap. Suaka Margasatwa Bukit Rimbang Bukit Baling di Sumatera bagian tengah merupakan sebuah kawasan penting untuk harimau baik pada tingkat lokal, regional, maupun global. Kawasan ini telah diakui sebagai sebuah kawasan prioritas jangka panjang Tiger Conservation Landascapes (TCL). Informasi dasar yang sahih mengenai populasi harimau dan mangsanya sangat dibutuhkan untuk pengelolaan efektif satwa tersebut dan kawasan habitatnya. Tujuan dari studi ini adalah untuk menghasilkan perkiraan kepadatan populasi harimau dan ketersediaan mangsanya di kawasan suaka margasatwa tersebut. Kami menggunakan perangkap kamera untuk mengumpulkan sampel gambar harimau dan mangsanya secara sistematis menggunakan kerangka kerja Spatial Capture Recapture (SCR). Kami memperkirakan kepadatan harimau dan menghitung angka keberhasilan perangkap atau trap success rate (TSR: gambar independen/100 hari aktif kamera) untuk satwa mangsa utama. Tiga blok di dalam suaka margasatwa telah disurvei dari tahun 2012 hingga 2015 mengakumulasikan keseluruhan 8,125 hari kamera aktif. Kami merekam 14 individu harimau termasuk tiga anak. Kami mendokumentasikan kepadatan tertinggi harimau (individu/100 km2) di blok sampling selatan (berdasarkan pendekatan analisa capture recapture tradisional (TCR) 1.52 ± SE 0.55; berdasarkan Maximum Likelihood (ML) SCR 0.51 ± SE 0.22) dan terendah di utara-timur (TCR: 0.77 ±SE 0.39; ML SCR: 0.19 ± SE 0.16). TSR tertinggi dari mangsa utama (ungulate besar dan primata) adalah di blok sampling utara-timur (35.01 ± SD 8.67) dan terendah adalah di blok sampling selatan (12.42 ± SD 2.91). Tingkat gangguan tertinggi, sebagaimana diindikasikan oleh TSR manusia, adalah di blok sampling utara-timur (5.45 ± SD 5.64) dan terendahnya di blok sampling selatan (1.26 ± SD 2.41). Hasil studi ini mengindikasikan bahwa gangguan manusia yang sangat tinggi sangat menentukan kepadatan harimau di kawasan ini, melebihi pengaruh dari ketersediaan satwa mangsa. Untuk memulihkan populasi harimau, disarankan beberapa strategi termasuk mengendalikan gangguan manusia dan perburuan hingga ke tingkat terendah, selain tetap memastikan ketersediaan satwa mangsa utama yang memadai.